GREEN INTELLECTUAL CAPITAL AND SUSTAINABILITY PERFORMANCE COMPANIES IN INDONESIA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the effect of green intellectual capital on the sustainability performanceof Indonesian companies. Green Intellectual Capital according to Chen (2008) is anintangible asset of a company, including knowledge, ability, experience and innovation in thefield of environmental protection. According to Chen (2008), green intellectual capital hasthree components, namely green human capital, green structural capital, and greenrelationship capital. All three are important factors to bring the company to a competitiveadvantage.The research was conducted by accessing financial reports from the Indonesiastock exchange website (www.idx.co.id). In this study, the method for analysis was carriedout in two ways, namely descriptive analysis and inferential analysis. Descriptive analysisdescribes each of the variables studied, while inferential analysis shows the relationshipbetween each variable obtained through data processing. The method of estimating the resultsof the study uses a complete panel data regression analysis (balanced panel data) with theStataSE 14 device to answer the research questions.From the results of the study, it is knownthat green human capital has a significant positive effect on sustainability performance, whilegreen structural capital has a significant positive effect on sustainability performance, andgreen relational capital has a significant positive effect on sustainability performance.Companies in Indonesia are more concerned about green intellectual capital. which consistsof Green human capital, Green structural capital and Green relatinal capital as indicators ofsustainability performance